PERAN MAJELIS TAKLIM DALAM MEMBINA KELUARGA SAKINAH MASYARAKAT MUSLIM DI KOTA PADANGSIDIMPUAN - Pulungan, Muhammad Yusuf (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractMethod taklim conducted through religious sermons, congregational worship activities, events wird, remembrance and prayer, the gathering / million-million cooperation and activities to help each other. Overall this method is very effective in building a happy family on the Muslim community in Padangsidimpuan. In other words, the methods applied in Padangsidimpuan taklim is significant in the lives of Muslim families to build Vegas, mawaddah wa Rahmah. Construction sankinah Family members taklim, measured by indicators of adherence to family members in their ritual daily prayers, polite attitude of family members, the ability to meet the material needs of the family members, the creation of good communication among family members and active members of the family in terms of religious and social groups in society, both positively and significantly improve the condition of happy family on the Muslim community in Padangsidimpuan. Based on statistical Product moment correlation was obtained between the two variables point at 0.764. This means that the relationship between the two variables is strong. Koefien point correlation also showed a positive direction. That is, when the assembly gathering in building harmonious family, the increased stress exercise, it would positively impact on the quality of the construction of harmonious family in the community in PadangsidimpuanKata Kunci : Majelis taklim, keluarga sakinah.